The Effect of Recycled High-Density Polyethylene (HDPE) as an Additional Binder in Porous Asphalt Pavement - L.A. Sofri; D. Ganesan; M.M. Al B. Abdullah; Chee-Ming Chan; M.H. Osman; J. Garus; S. Garus (Archives of Metallurgy and Materials)
Porous asphalt has excellent permeability and larger air voids. Due to the low stability strength of asphalt binder with aggregates, Malaysia uses porous asphalt roads for lightweight vehicle road transportation. Numerous studies indicate utilizing Recycled High-Density Polyethylene in porous asphalt road surface. As a result, it was utilised as an additional binder material to enhance the asphalt binder. The main purpose of this study is to investigate the stability of modified porous asphalt samples and evaluate the optimum percentage of HDPE plastic waste from 3%, 6% and 9%. The aggregates, asphalt properties, Marshall Parameters and waster absorption test are in comply with JKR Standard and PWD 2008. At 3% of plastic addition has improved the stability of porous asphalt specimens. Adding plastic waste as a binder helps strengthen asphalt binding.